IMPLEMENTASI KEBIJAKAN JAMINAN SOSIAL KETENAGAKERJAAAN PADA SEKTOR PUBLIK (Studi tentang Aspek Penahapan Kepesertaan BPJS Ketenagakerjaan di Universitas Brawijaya Malang) - Zuhad, Shofi Fairuz (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
Implementation of Social Security Policy in Public Sector Study in Brawijaya University Malang. The establishment of Social Security Provider through Law Number 24 Year 2011 on National Social Security Provider is the implementation of national social security program which aims to provide welfare guarantee for all Indonesian people. Employers other than state organizers in accordance with the scale of their business since July 1, 2015 must register its employees to be a participant in Social Security Provider of Manpower (BPJS Ketenagakerjaan). Policy for registration stages as BPJS Ketenagakerjaan participants are set in the Presidential Regulation No. 109 Year 2013. Educational institutions are targeted by BPJS Ketenagakerjaan because in it has a workforce that has not get a guarantee for his work. Brawijaya University has received socialization from BPJS Ketenagakerjaan of Malang and approved the existence of the policy. As a State University, Brawijaya University has a lot of manpower, but still has not enlisted its workers to become a participant in BPJS Ketenagakerjaan. Â  Key words: Implementation, Policy of Manpower Social Security Program, Membership Staging